1990
DOI: 10.1038/icb.1990.25
|View full text |Cite
|
Sign up to set email alerts
|

Murine candidiasis: Susceptibility is associated with the induction of T cell‐mediated, strain‐specific autoreactivity

Abstract: Summary Inbred mice can be classified as susceptible or resistant to systemic infection with the yeast Candida albicans by histopathological evaluation of tissue lesions. Candida-specific memory T cell responses generated by resistant BALB/c mice are vigorous and sustained, whereas those displayed by susceptible CBA/H mice are weak. When spleen cells from immune mice were activated by culture with Candida antigens in vitro, and injected into syngeneic and allogeneic recipients in the absence of further antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
(18 reference statements)
1
10
1
Order By: Relevance
“…In this study, we tested the Fba peptide in C57BL/6 mice, another common inbred mouse strain, but with an MHC haplotype and immunophenotype distinct from those of BALB/c mice (35). These two strains also differ in their resistance or susceptibility to experimental disseminated candidiasis (2)(3)(4). In addition to mouse strain differences with respect to a Th1 (C57BL/6) or Th2 (BALB/c) bias, the strains differ in their macrophages' ability to be activated (6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we tested the Fba peptide in C57BL/6 mice, another common inbred mouse strain, but with an MHC haplotype and immunophenotype distinct from those of BALB/c mice (35). These two strains also differ in their resistance or susceptibility to experimental disseminated candidiasis (2)(3)(4). In addition to mouse strain differences with respect to a Th1 (C57BL/6) or Th2 (BALB/c) bias, the strains differ in their macrophages' ability to be activated (6).…”
Section: Resultsmentioning
confidence: 99%
“…(A) Use of MAb E2-9 in confocal microscopic analyses showed that the peptide Fba is expressed on the fungal surface and E2-9 can directly bind to both yeast and hyphal forms of the fungus. MAb B6.1, which is specific to ␤-(Man) 3 , was used as a positive control. (B) MAb E2-9 binding to the Fba peptide expressed on the C. albicans cell surface was further confirmed by the use of flow-cytometric analysis.…”
Section: Vol 18 2011 Vaccine and Antibody Protection Against Candidmentioning
confidence: 99%
See 1 more Smart Citation
“…Such paradoxical findings may be explained by deriving data from different experimental models (guinea pigs, hamsters, rats or mice), different routes of challenge (oral, intranasal, intraperitoneal or intravenous challenges), different doses of C. albicans and even the choice of media used to grow the initial inocula (Odds et al, 2000). Susceptibility and survival of the animal host during disseminated candidiasis has also been shown to depend upon the strain of mouse used (Ashman, 1990;Ashman & Papadimitriou, 1987;Hector et al, 1982); however, some groups have reported that BALB/c mice are more susceptible to intravenous challenge with C. albicans than C57BL/6 mice (Ashman & Papadimitriou, 1987;Marquis et al, 1986), while others have shown no significant difference in their susceptibility (Hector et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages also contribute to host resistance, and show considerable regional and In summary, these data demonstrate that the control of tissue destruction associated with systemic C. albicans infection is dependent on both CD4' and CD8' T lymphocytes. Furthermore, the development and expression of CD4' cell function can be influenced by the genetic endowment of the mouse, and this may be related to down regulation of T cell memory (Ashman, 1990a) and the potential to express immunopathological activity (Ashman, 1990b) in the CBA/CaH mouse strain. The immunological and genetic determinants of this regulatory process are the subject of current investigations.…”
Section: Passive Transfer Experimentsmentioning
confidence: 99%